Searching for a Global alpha-nucleus Potential for Astrophysical Applications - Spyrou, A.; Lagoyannis, A.; Zarkadas, Ch.; Harissopulos, S.; Becker, H.-W.; Rolfs, C.; Demetriou, P. (HNPS Advances in Nuclear Physics, 2020)
This contribution reports on a systematic investigation of in-beam cross-section measurements of (α,γ) reactions, carried out using a 4π calorimeter. The results are compared to the predictions of the Hauser-Feshbach (HF) theory. This com parison puts some constraints on the relevant nuclear properties entering the HF calculations.